Immediate and Catastrophic Antibody‐Mediated Rejection in a Lung Transplant Recipient With Anti–Angiotensin II Receptor Type 1 and Anti–Endothelin‐1 Receptor Type A Antibodies. Issue 2 (31st October 2016) - Cozzi, E.; Calabrese, F.; Schiavon, M.; Feltracco, P.; Seveso, M.; Carollo, C.; Loy, M.; Cardillo, M.; Rea, F.
Abstract : Preexisting donor‐specific anti‐HLA antibodies (DSAs) have been associated with reduced survival of lung allografts. However, antibodies with specificities other than HLA may have a detrimental role on the lung transplant outcome. A young man with cystic fibrosis underwent lung transplantation with organs from a suitable deceased donor. At the time of transplantation, there were no anti‐HLA DSAs. During surgery, the patient developed a severe and intractable pulmonary hypertension associated with right ventriular dysfunction, which required arteriovenous extracorporeal membrane oxygenation. After a brief period of clinical improvement, a rapid deterioration in hemodynamics led to the patient's death on postoperative day 5. Postmortem studies showed that lung specimens taken at the end of surgery were compatible with antibody‐mediated rejection (AMR), while terminal samples evidenced diffuse capillaritis, blood extravasation, edema, and microthrombi, with foci of acute cellular rejection (A3). Immunological investigations demonstrated the presence of preexisting antibodies against the endothelin‐1 receptor type A (ETA R) and the angiotensin II receptor type 1 (AT1 R), two of the most potent vasoconstrictors reported to date, whose levels slightly rose after transplantation. These data suggest that preexisting anti‐ETA R and anti‐AT1 R antibodies may have contributed to the onset of AMR and to the catastrophic clinical course of this patient. Abstract : The authors investigate the cause of the immediate and catastrophic antibody‐mediated rejection in a lung transplant recipient with no donor‐specific anti‐HLA antibodies and find that preexisting anti–angiotensin II receptor type 1 and anti–endothelin‐1 receptor type A antibodies may play a detrimental role.